Cambial activity in dry and rainy season on branches from woody species growing in Brazilian Cerrado - Marcati, Carmen R. [UNESP]; Machado, Silvia R. [UNESP]; Podadera, Diego Sotto; Lara, Natalia O. Totti de [UNESP]; Bosio, Fabio [UNESP]; Wiedenhoeft, Alex C. [UNESP] (Elsevier, 2016)
Seasonal cambial activity was investigated in one- to three-year-old branch modules (branch constructional units) of ten woody species from cerrado sensu stricto, a savanna-like ecosystem, of southern Brazil. Relationships between cambial activity and environmental factors (precipitation, temperature, day length) and leaf production were tested using generalized linear mixed model. Regardless the plant habit and leaf shedding patterns, cambial activity (about 5 months) corresponded to the core of the rainy season (when at least 66% of the annual precipitation had been reached), even though there was some delay or advance in the timing of cambial activity depending on the branch age or species. Cambial activity began in the dry season and ceased before the end of rainy season. Although cambial activity has been positively correlated with day length, precipitation, temperature, and budding for all species, day length, among the assessed factors, seems to be the best predictor of onset and cessation of cambial activity in the branch modules of cerrado species.
Keywords: Budding; Cambium; Photoperiod; Precipitation; Savanna-like ecosystem; Temperature